Horizontal alliances as an alternative to autonomous production: product expansion mode choice in the worldwide aircraft industry 1945–2000 - Garrette, Bernard; Castañer, Xavier; Dussauge, Pierre (Strategic Management Journal, 2009)
Abstract This study investigates why firms choose to undertake product expansion through alliances with competitors rather than on their own. We highlight product heterogeneity as a determinant of this make or ally choice. We propose that firms turn to horizontal alliances in order to implement product expansion projects that require greater resources than those available to them. More precisely, we hypothesize that a firm is more likely to launch a new product through a horizontal alliance rather than autonomously when the resource requirements of the project are greater, the resources available to the firm are more limited, there is a mismatch between resource endowment and requirement, and the firm's collaborative competence allows it to better cope with the interorganizational concerns that collaboration with competitors raises. We find support for our arguments on a sample of 310 new aircraft developments launched between 1945 and 2000, either by a single prime contractor or as a horizontal alliance in which prime contractorship is shared with another industry incumbent. Copyright © 2009 John Wiley & Sons, Ltd.